Fatal anaphylaxis registries data support changes in the who anaphylaxis mortality coding rules. Issue 1 (December 2017) - Tanno, Luciana; Simons, F.; Annesi-Maesano, Isabella; Calderon, Moises; Aymé, Ségolène; Demoly, Pascal
Abstract Anaphylaxis is defined as a severe life-threatening generalized or systemic hypersensitivity reaction. The difficulty of coding anaphylaxis fatalities under the World Health Organization (WHO) International Classification of Diseases (ICD) system is recognized as an important reason for under-notification of anaphylaxis deaths. On current death certificates, a limited number of ICD codes are valid as underlying causes of death, and death certificates do not include the word anaphylaxisper se . In this review, we provide evidences supporting the need for changes in WHO mortality coding rules and call foraddition of anaphylaxis as an underlying cause of death on international death certificates . This publication will be included in support of a formal request to the WHO as a formal request for this move taking the 11th ICD revision.